PERAN DAN DAMPAK KONFLIK TENURIAL KEHUTANAN BAGI PENGELOLAAN KEANEKERAGAMAN HAYATI DI KAWASAN CAGAR BIOSFER DI JAWA TIMUR Role and Impact of Forestry Tenurials Conflict to The Management of Biodiversity in Biosphere Reserve in East Java - Luchman Hakim; Irena Aldianoveri; Iman Kusuma Bangsa; Dodit Ari Guntoro (Lambung Mangkurat University-Indonesia, 2018)
Bromo Tengger Semeru Arjuno Biosphere Reserve and Blambangan Biosphere Reserve in East Java was established as models for sustainable development area. Threats and opportunities in biosphere reserve management are including tenurials problems that are potentially able to disturb the conservation agenda in core zone of biosphere reserve. The aims of the research are to describe the biosphere reserve in East Java and to identify tenurials problem in biosphere reserve. It is become key for the successful of biosphere reserve programs. Result of the study shows that Bromo Tengger Semeru Arjuno Biosphere Reserve and Blambangan Biosphere Reserve are the important area for conservation and sustainable development in East Java. Tenurials conflict occurs and there are some aspect contributes to the conflict. The important aspect contribute to tenurials conflict includes economic needs, policy overlap, misperception about land status and ownership, misinformation and communication, relationship disharmony between party in community, and education quality of human resources surrounding biosphere reserve area. Tenurials conflict mitigation is one of the key for successful biosphere reserve management. In such mitigation, fostering multi-sectorial approach and involving all of the party into integrative conflict mitigation strategy is important.Keywords: tenurial conflict; sustainable development; Biosphere reserve . Cagar Biosfer Bromo Tengger Semeru Arjuno (CB-BTSA) dan Cagar Biosfer Blambangan (CBB) di Jawa Timur diharapkan dapat menjadi model pengelolaan kawasan secara berkelanjutan. Kendala dan tantangan dalam pengelolaan cagar biosfer tersebut adalah permasalahan tenurial yang dapat mengannggu kegiatan konservasi di kawasan inti dari cagar biosfer. Tujuan penelitian ini adalah mendeskripsikan cagar biofer di Jawa Timur dan mengetahui permasalahan tenurial yang terjadi di kawasan CB-BTSA dan CB-B yang menjadi kunci dalam keberhasilan pengelolaan cagar biofer. Penelitian ini menunjukkn bahwa CBBTSA dan CB-B adalah kawasan strategis dalam program konservasi dan pembangunan berkelanjutan di JAwa Timur. Konflik tenurial masih terjadi, dan beberapa aspek yang melatar belakangi terjadinya konflik. Beberapa aspek tersebut antara lain adalah tuntutan ekonomi, tumpang tindih kebijakan, pemahaman yang salah akan status tanah, mis-informasi dan komunikasi, disharmonisasi hubungan komponen masyarakat, penegakan hukum, dan kualitas pendidikan masyarakat sekitar cagar biosfer. Penangan konflik tenurial menjadi salah satu kunci dari pengelolaan cagar biofer. Penanganan konflik tersebut mutlak dilakukan pendekatan multisektorial dan melibatkan semua komponen masyrakat.Kata kunci: konflik lahan; pembangunan berkelanjutan; Cagar Biosfer